Inovasi Teknologi Pelayanan Publik Dalam Implementasi E-Government Studi Kasus Aplikasi Sakedap di Kabupaten Bandung - K, Khoerunisa; Najatin, Amelia; Anwar, Faqih Eka Muhammad; Santa, Rahmat; Yusuf, Junjunan Maulana (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The SAKEDAP application or the Integrated Population Service System carried out by the Population and Civil Registration Office of Bandung Regency to organize a service for the people of Bandung Regency itself. The sources that are relevant to the topic of study, namely regarding Public Service Technology Innovation in E-Government Implementation, will be used as references in writing the article. The data collected is sourced from Google Scholar. Effectiveness of the SAKEDAP Application in Population Administration Services If we look at the positive impact of this application, it can facilitate the community in obtaining population administration services. Apart from that, this application was initially made to prevent the spread of the Covid-19 virus in the DISDUKCAPIL environment in Bandung Regency and speed up the service process to the community. This SAKEDAP application has not run so optimally, it can be seen from the Rating and Review of this application, due to the many complaints from the community because of the obstacles faced. This obstacle is caused because some people have difficulty uploading files, lack of chat features, and not a few people complain about queue numbers that are always full.